Theoretical investigation of spectroscopic properties of W26+ in EBIT plasma. (5th June 2015) - Jonauskas, V; Kynienė, A; Rynkun, P; Kučas, S; Gaigalas, G; Kisielius, R; Masys, Š; Merkelis, G; Radžiūtė, L
Abstract: Energy levels, radiative transition wavelengths and probabilities have been studied for the ion using multiconfiguration Dirac–Fock and Dirac–Fock–Slater methods. Corona and collisional-radiative models have been applied to determine lines and corresponding configurations in a low-density electron beam ion trap (EBIT) plasma. Correlation effects for the 4f 2, , ( ), ( ) configurations have been estimated by presenting configuration interaction strengths. It was determined that correlation effects are important for the transitions corresponding to weak electric octupole transitions in a single-configuration approach. Correlation effects influence the transitions by increasing transition probabilities by an order of magnitude. Identification of some lines observed in fusion plasma has been proposed. Spectra modeling shows strong increase of lines originating from the transitions. Other transitions from the 10–30 nm region can be of interest for the EBIT plasma.